2016
DOI: 10.1071/ah15080
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision for allied health staff: necessary but not sufficient

Abstract: Objectives. The aim of the present study was to explore the perspectives of allied health professionals on appropriate content for effective clinical supervision of staff.Methods. A set of statements regarding clinical supervision was identified from the literature and confirmed through a Q-sort process. The final set was administered as an online survey to 437 allied health professionals working in two Australian health services.Results. Of the 120 respondents, 82 had experienced six or more clinical supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Ensuring that guidelines acknowledge direct models of supervision, involving observation of supervisees’ clinical practice, might have a positive effect on patient safety and care [44, 45]. Some allied health professionals do not believe that observation of supervisees’ clinical practice is an aspect of clinical supervision [46]. This is despite the role of clinical supervision as a form of clinical governance [1], and evidence showing an association between direct models of supervision and improved patient safety and care [44, 45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring that guidelines acknowledge direct models of supervision, involving observation of supervisees’ clinical practice, might have a positive effect on patient safety and care [44, 45]. Some allied health professionals do not believe that observation of supervisees’ clinical practice is an aspect of clinical supervision [46]. This is despite the role of clinical supervision as a form of clinical governance [1], and evidence showing an association between direct models of supervision and improved patient safety and care [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the role of clinical supervision as a form of clinical governance [1], and evidence showing an association between direct models of supervision and improved patient safety and care [44, 45]. Clear organisational guidelines that outline the role of clinical supervision in ensuring high quality patient care may positively influence the acceptability and practice of the direct models of clinical supervision by all allied health professionals, and enhance patient care [46].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [ 31 , 118 ] (0.7%) translated their Q-methodology findings into a survey, referring to the process as ‘Q2S’. Through a Q-methodological study, Baker et al [ 31 ] identified three viewpoints (factors) on healthcare priorities and resource allocation.…”
Section: Methodsmentioning
confidence: 99%
“…In the same article, they then adapted the Q-sorting task into a survey to identify the distribution of each of the three viewpoints in a larger population. Leggat et al [ 118 ] identified two factors regarding the content of clinical supervision for allied health staff. The results were used to develop a survey on the content, outcomes and understanding of clinical supervision.…”
Section: Methodsmentioning
confidence: 99%
“…Across the studies reviewed, professional supervision was noted to be an important process to enable professionals to improve the quality of patient care. 19,21,22,26 Evidence based quality care is a key aspect of all health professionals' roles. The research noted that professional supervision can contribute to professional growth which in turn will ensure delivery of high-quality care.…”
Section: Support For Quality Patient Carementioning
confidence: 99%